The Relationship Between The Duration of Three-Month Injectable Contraception Use And Blood Pressure Changes - Hikmatun Nuriah Wulandari; Sugijati; Gumiarti (Indonesian Journal Publisher, 2026)
Introduction: DMPA injectable contraception has side effects of changes in blood pressure. DMPA can cause changes in blood pressure, especially if used in the long term. Injectable contraceptive users in Jember Regency (50.9%) and Mumbulsari District in 2024 (56%). The results of a preliminary study at PMB Citra Dwi Lestari on 10 long-term 3-month injectable contraceptive acceptors showed that 7 people experienced changes in blood pressure, 6 acceptors experienced an increase and 1 acceptor experienced a decrease in blood pressure and 3 acceptors did not experience changes in blood pressure. The study aims to determine the relationship between the length of use of 3-month injectable contraceptives and changes in blood pressure. Methods: Correlation research design with a Cross Sectional approach on 70 3-month injectable contraceptive acceptors at PMB Citra Dwi Lestari on February 26-March 26, 2026, Purposive Sampling technique, Research instruments using observation sheets. Statistical analysis using the chi square test. Results: Based on the results of the Chi Square test on 70 respondents, a p-value of 0.001 (<0.05) and a correlation coefficient of 0.368 were obtained, so there is a fairly strong relationship between the duration of use of 3-month injectable contraception and changes in blood pressure. Conclusion : The longer the use of 3-month injectable contraception can increase blood pressure due to the effect of the progesterone hormone on the renin-angiotensin system, so acceptors are advised to have their blood pressure checked regularly. Keywords: Duration of Contraceptive Use, Changes in Blood Pressure